2022
DOI: 10.1094/pbiomes-10-21-0064-r
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Rooted Plant Species Recruit Distinct Bacterial Communities in the Subsoil

Abstract: Deep-rooted plants can obtain water and nutrients from the subsoil, making them resilient to climatic changes. Plant growth and health may depend on interactions with root-associated bacteria, but the composition and assembly dynamics of deep root-associated bacterial communities are unknown, as are their ability to supply plants with nitrogen (N). Here, we investigated the root-associated communities of the three deep-rooted perennial crops, lucerne (Medicago sativa), intermediate wheatgrass (Thinopyrum inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Comparable to the current study, a previous investigation observed similar relative abundance patterns of nirK gene copy numbers in wheat seedlings [ 60 ]. In adult intermediate wheatgrass roots, however, they were almost 100-fold higher [ 15 ]. Though, the relative abundance of nirK and nifH gene copy numbers decreased over time in wheat and Brassica seedlings respectively, suggesting that the sampling timepoint may have a substantial influence on their occurrence [ 57 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparable to the current study, a previous investigation observed similar relative abundance patterns of nirK gene copy numbers in wheat seedlings [ 60 ]. In adult intermediate wheatgrass roots, however, they were almost 100-fold higher [ 15 ]. Though, the relative abundance of nirK and nifH gene copy numbers decreased over time in wheat and Brassica seedlings respectively, suggesting that the sampling timepoint may have a substantial influence on their occurrence [ 57 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information on the positive ecosystem services of intermediate wheatgrass is increasingly available, however, knowledge of the microbiome of this crop is scarce. A limited number of studies addressed the microbiome of intermediate wheatgrass, targeting only below-ground compartments [ 14 , 15 ]. Perenniality and management influence the communities of soil nematodes, earthworms and bacteria associated with intermediate wheatgrass and the plants generally sustain more complex food webs compared to annual wheat [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oft-cited methods of root harvesting are shovelomics [ 23 , 24 ], trenching (pioneered by [ 25 ]) [ 18 ], and coring [ 26 ]. These methods are labor-intensive and shovelomics, for example, requires destruction of the growth environment and removal of the sample plants by removing the root crown.…”
Section: Root Acquisitionmentioning
confidence: 99%